In-silico analysis of WRKY Transcription Factors gene family in healthy and malformed stages of mango (Mangifera indica) - YADAV, ASHOK; USHA, K; JAYASWAL, PAWAN KUMAR (The Indian Journal of Agricultural Sciences, 2019)
WRKY proteins play crucial roles in plant defense regulatory networks, development process and physiological programs including responses to several biotic and abiotic stresses. Evalutionary analysis revealed, WRKY genes were categorized into the four major groups. In developed phylogenetic tree, group-D contain highest number (15) of WRKY genes followed by group-B (10), group-A (7), and group-C (6). Several number of CRE’s were identified from mango transcriptome belonging to different categories like light responsiveness, hormone responsive, bioticstress responsive, biotic stress responsive, binding, plant development, transcription and circadian control. Among the10 stable genes observed in transcriptome, nine genes had negative Z-score indicating that these structures identifiedfor the proteins are reliable. Motif analysis indicated that the per cent occurrence of all the five motifs were higher in WRKY genes of malformed tissues compared to WRKY genes of healthy tissues. The uniquely identified CRE’s (Healthy stages: AC-II, GCC box, OBP; Malformed stages: Aux-RR-core, AC-I, 3-AF1 binding site, CAT-box, MNF1 and rbcS-CMA7a.), defense and stress responsiveness (TC-rich repeats) and fungal elicitor (Box-W1) related cis-regulatory elements will provide insight to solve the problem of mango malformation. The identified information regarding the WRKY Transcription Factor from mango transcriptome will serve as a valuable information for mango breeding against malformation.